MENINGKATKAN KEPUASAN PELANGGAN DIBELMOND JIMBARAN PURI BALI MELALUI LEADING QUALITY ASSURANCE (LQA) - Sukadana, I Gede; Astawa, I Ketut (JURNAL KEPARIWISATAAN, 2016)
Improving customersâ satisfaction is important in the hospitality industry. On the other hand, quality services encourage customer satisfaction. Therefore, offering product (tangible) and services (intangible) to customers need to be standardized.Belmond Jimbaran Puri Bali committed to excellent serviceby implementing LQA standard.LQA standard is specializes in providing quality assurance audits, benchmarking analysisand training services tothe luxury hospitality industry. This research is aiming to analyse the implementation of LQA standard to improve the customersâ satisfaction in front office department. Data is analysed by using Context, Input, Process, and Output (CIPP) methodand supported by SPSS 17.0for windows. The finding of implementing LQA standard is in excellent categories. The finding proved that LQA standard is well implemented by Belmond Jimbaran Puri Bali management.